2010
DOI: 10.1016/s1130-1473(10)70128-7
|View full text |Cite
|
Sign up to set email alerts
|

Cranio-thoracic bullet migration over a period of 27 years: case report

Abstract: SummaryWe report the case of a 36 year old woman that was hurt in the head with a lost bullet while walking through the street when she was 9 years old. On admission, the patient was fully conscious with no neurological deficits. Skull radiography showed the intracranial bullet but she was dispatched after 24 hours of observation without neurological deterioration. Six months later she suddenly presented quadriplegia and after one year of rehabilitation she recovered the mobility and strength in all her limbs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…The time course for migration ranges from 2 days to 3 months. [2,7,10] The course of a ricochet bullet is different from migration movement of a retained bullet. A ricochet bullet changes its direction after hitting the wall of the cranium or spinal canal, whereas retained bullet migration may be affected by several factors, such as gravitational factors.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The time course for migration ranges from 2 days to 3 months. [2,7,10] The course of a ricochet bullet is different from migration movement of a retained bullet. A ricochet bullet changes its direction after hitting the wall of the cranium or spinal canal, whereas retained bullet migration may be affected by several factors, such as gravitational factors.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Gravitational force acting on the bullet, which is denser than the surrounding medium, has been suggested as a cause for migration caudally by the effect of gravity related to the position of the body, especially in the absence of significant cranial swelling. [7,10] Castillo-Rangel and Salvati [2,12] suggested that the ventricular system provides transport of the bullet from one area of the brain to another. Cerebrospinal fluid (CSF) flow and pulsation will facilitate the bullet's movement within the ventricle.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations